Identifikasi Plankton Sebagai Bioindikator Tingkat Pencemaran Di Sungai Murak Kabupaten Merangin - Rozana Zuhri (BIOCOLONY, 2018)
Rivers have an important role in human life. They are the living place for the amount of biodiversity, but now the river has been polluted due to human activities. The object of this research is to know Murak river quality based on plankton diversity. Other than that, to determine the factors that influence water pollution and to know the level of water pollution based on biological, physical and chemical indicators. Sampling is done in Murak river of Merangin. The identification of plankton and water analysis is done at the Biology Education Laboratory. From the results of the study, there were 24 genus of plankton found, of the 24 genera there are 7 genera that enter in the category of pollution indicator that is Nitzschia sp, Chlamydomonas, Spirogyra , Chlorococcum, Euglena, Oscillatoria, Pyrobotris dan Anabaena.. And based on the index of diversity (H ') is in the value of 1-3 so it is concluded that the waters of the Murak river of Merangin have been polluted.